Neutrophil metabolism in the cancer context. (October 2021) - Bodac, Anita; Meylan, Etienne
Abstract: Neutrophils are critical innate immune cells for the host anti-bacterial defense. Throughout their lifecycle, neutrophils are exposed to different microenvironments and modulate their metabolism to survive and sustain their functions. Although tumor cell metabolism has been intensively investigated, how neutrophil metabolism is affected in cancer remains largely to be discovered. Neutrophils are described as mainly glycolytic cells. However, distinct tumor-associated neutrophil (TAN) states may co-exist in tumors and adapt their metabolism to exert different or even opposing activities ranging from tumor cell killing to tumor support. In this review, we gather evidence about the metabolic mechanisms that underly TANs' pro- or anti-tumoral functions in cancer. We first discuss how tumor-secreted factors and the heterogenous tumor microenvironment can have a strong impact on TAN metabolism. We then describe alternative metabolic pathways used by TANs to exert their functions in cancer, from basic glycolysis to more recently-recognized but less understood metabolic shifts toward mitochondrial oxidative metabolism, lipid and amino acid metabolism and even autophagy. Last, we discuss promising strategies targeting neutrophil metabolism to combat cancer.